2020
DOI: 10.1016/j.waojou.2019.100092
|View full text |Cite
|
Sign up to set email alerts
|

The burden of asthma in an inner-city area: A historical review 10 years after ISAAC

Abstract: Background: According to the International Study of Asthma and Allergies in Childhood (ISAAC) methodology, in 2003, the prevalence of asthma symptoms in children 6-7 years old and adolescents 13-14 years old was 11.6% and 13.7%, respectively. Since then, the number of asthma cases has increased worldwide. The study was conducted in several districts in northern Mexico City to evaluate the prevalence of asthma in these age groups and examine possible risk factors. The data were compared to the 2003 results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
0
25
1
4
Order By: Relevance
“…9,10 Finally, 'Global Asthma Network Mexico' reported the most recent asthma prevalence in children aged 6-7 and 13-14 years: 5.8% and 7.5%, respectively. 11 This prevalence contradicted with the one observed in our study (3.7%).…”
Section: Resultscontrasting
confidence: 99%
“…9,10 Finally, 'Global Asthma Network Mexico' reported the most recent asthma prevalence in children aged 6-7 and 13-14 years: 5.8% and 7.5%, respectively. 11 This prevalence contradicted with the one observed in our study (3.7%).…”
Section: Resultscontrasting
confidence: 99%
“…Del-Rio-Navarro and collaborators observed that the prevalence of asthma symptoms increased by 3.8% in the group of school children and decreased one percent in the adolescents' group. 11 ISAAC Phase Three also reported several parental and child characteristics associated with asthma symptoms in school children. Such factors included parental smoking 12 ; use of paracetamol in the first year of life as well as dose-dependent current use of paracetamol 13 ; use of antibiotics in the first year of life 14 ; dietary habits 15 16 ; overweight and obesity 17 and sedentarism.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 , 16 The prevalence of asthma in the general population in Italy, Spain, and Ireland is 6.0%, 5.0%, and 7.0%, respectively 12 , 17 , 18 ( Fig 1 , A and B ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26
Fig 1 Asthma prevalence. A, Countries with high prevalence of asthma among COVID-19 comorbidities in comparison with asthma prevalence in the general population (high asthma-COVID-19 zone) are marked in red color.
…”
Section: Global Epidemiologymentioning
confidence: 99%
“…B, Asthma prevalence (%) among patients with COVID-19 in comparison with the general population in various countries. 12 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Global Epidemiologymentioning
confidence: 99%